Right to a fair trial : Article 6 of the European Convention on Human Rights - Leanza, Piero; Pridal, Ondrej (Alphen aan den Rijn, The Netherlands : Wolters Kluwer Law & Business : Kluwer Law International, 2014)
The right to a fair trial is a basic principle of the rule of law in democratic societies, securing the right to a proper administration of justice. What makes the European Convention on Human Rights (ECHR) special in comparison with other international instruments is the possibility granted to any individual to file a complaint with the European Court of Human Rights (ECtHR). ECtHR cases are imbued with a 'preventive' impact: judges, courts, and tribunals in Signatory States to the ECHR are required to take into consideration Article 6 and the ECtHR's case law when handling and deciding cases. The copious case law of the ECtHR has led to an expansion of the number of specific rights deserving protection under the general category of the right to a fair trial, thus greatly enhancing the fundamental human rights that are listed in almost all international conventions and numerous state constitutions --
The right to a fair trial / Piero Leanza & Ondrej Pridal -- Article 6 ECHR / Piero Leanza -- Particular aspects of the right to a fair trial / Piero Leanza -- The right to a fair trial in criminal proceedings / Piero Leanza -- Conflict between particular aspects of the right to a fair trial / Ondrej Pridal -- The right to a fair trial in practice / Ondrej Pridal -- Appendix: Convention for the Protection of Human Rights and Fundamental Freedoms.
Includes bibliographical references (pages 253-257) and index.
Keywords: d; f; Fair trial -- Europe; 86.81 human rights; UE/CE Droit; 2; 2; Proces; Conflit des lois; Fair trial; Europe